Building Peace Values Through The Values of Religious Hospitality - Umar Said Wijaya; Musa Asy'arie; Waston Waston (Universitas Muhammadiyah Ponorogo, 2023)
Religious harmony is a concept of values that allows a person to live in a multicultural society in peace and security. Instilling religious values of harmony can be integrated into the education system. This study aims to analyse the religious values of harmony in the higher education system. The research was conducted at Darussalam Gontor University, Ponorogo. Using a descriptive qualitative research method with a case study approach, data were obtained through direct observation at research locations and interviews with university leaders, directors of Islamic boarding schools, heads of study programmes, heads of research and community service institutions, lecturers, and students. The results of the study show that the integration pattern applied is multi-value and multi-system integration. This tertiary institution has implemented education on harmonious religious values in a pesantren-based higher education system through the stages of harmony knowing, harmony feeling, harmony action, harmony controlling, and harmony evaluation. The core values of Islamic boarding schools are summarised in the Five Spirits of Pesantren (Islamic Boarding Schools), which include sincerity, simplicity, independence, ukhuwwah Islamiyyah, and freedom, supported by the values of peace, equality, the sacredness of life, respect and appreciation, honesty, waqf, and wisdom. These values are based on obedience, faith, and servitude to Allah SWT, which are extracted from the Qur'an and hadith. Instilling these values uses the integration model of four educational centres, namely mosques, dormitories, classes, and the environment/nature, with attention to the development of intellectual, spiritual, emotional, and skill potential, with the hope that campus life can be created in a way that is scientific and practical, harmonious and competitive.Â